STRUKTUR KOMUNITAS IKAN DI DANAU JEMUT KABUPATEN SINTANG - Stepanus, Oka; Soetignya, Widadi Padmarsari; Hadinata, Fitra Wira (Akuatik Tropis (Akuatrop): Journal of Tropical Aquatic Resource Management (ISSN:3063-7414), 2024)
The purpose of this research is to know the fish community structure in West Kalimantan Province's Jemut Lake, Sintang District. Three sampling locations were used during the research's September to October 2022 execution. Once each week, sampling was done using trawls, nets, and fishing rods. When collecting fish samples at the research site, measurements of the water quality were made on the spot. The findings revealed that there were 17 fish species from 9 families. The species Kriptopterus limpok had the highest relative abundance value (18.66%), whereas Luciosoma trinema and Osphronemus goramy had the lowest species composition (0.20%). At every station, the value of diversity and uniformity is moderate, and the distribution pattern is balanced. The assessment outcomes of numerous water quality parameters indicate water conditions that are suitable for fish life.